Alternative therapy interaction with warfarin: what doctors should know - T. B. Kozlova; T. V. Taratuta; M. B. Aksenova; T. V. Khlevchuk (Кардиоваскулярная терапия и профилактика, 2010)
Warfarin effectiveness and safety is substantially affected by concurrent therapy. This paper reviews the main mechanisms of warfarin interactions with other agents, which underlie adverse effect development: platelet dysfunction, gastro-intestinal effects, suppressed intestinal synthesis of vitamin K, disturbed warfarin metabolism, or disrupted vitamin K cycle. The main medication groups, affecting warfarin effectiveness and safety, are presented. The effects of foods, supplements, and herbal medications on anticoagulant effect of warfarin are discussed.